SIPPA sebagai Pelaporan Pengendalian dan Evaluasi Kebijakan Perencanaan Program dan Anggaran - Syukur, Abdul (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This policy paper aims at developing a Program and Budget Reporting Information System or Sistem Informasi Pelaporan Program dan Anggaran (SIPPA) as a Reporting on Control and Evaluation of Program and Budget Planning Policies at Badan Litbang and Diklat Kementrian Agama. In collecting information for analysis, the authors conducted discussion and interview methods, studied regulations/laws, and explored sites on the internet. The stages of system development that have been done are, system planning, system requirements analysis, system design, system selection, system implementation and system testing. The results of the research are a web-based Program and Budget Reporting Information System Application or Sistem Informasi Pelaporan Program dan Anggaran (SIPPA) for Badan Litbang and Diklat Kementrian Agama that can be accessed online. This system will facilitate every level of leadership in reporting, controlling and evaluating Program and Budget Performance Achievements in accordance with their authority, as well as in making program and budget planning policies for the following year. Keywords: Reporting; Control; Evaluation; Planning